Healthcare Service Quality Between BPJS and Non-BPJS Patients as a Challenge to Equity in Public Services at Government Hospitals - Adinda Syafitri; Aisyah Miftahul Jannah; Shelma Nayla Fitri; Shalsa Olivia; Yulia Hanoselina; Yuliarti Y (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Health services, as part of public services, are the state's responsibility to ensure the fulfillment of citizens' basic rights through the BPJS Kesehatan program to realize equitable and just access to health care. However, in practice in government hospitals, there is still a perception of differences in service quality between BPJS and non-BPJS patients, particularly in waiting times, administrative procedures, and the attitudes of health workers. This study aims to examine the gap in health service quality based on the SERVQUAL theory, which includes tangibles, reliability, responsiveness, assurance, and empathy, and examine its implications for the principle of public service fairness. The approach used in this study is qualitative with a literature study method, where data is collected from various sources such as scientific journals, books, scientific articles, and documents related to health services. The results of the study indicate that although service standards normatively do not differentiate between types of participants, in implementation, service disparities are still found that have the potential to hinder distributive justice and equal access to health services. Therefore, strategic steps are needed in the form of strengthening oversight mechanisms, increasing human resource capacity, and commitment to the principles of good governance to realize equitable and non-discriminatory health services.